Fluorescence-Based Ratiometric Analysis of Sperm Centrioles (FRAC) Finds Patient Age and Sperm Morphology Are Associated With Centriole Quality - Turner, Katerina A.; Fishman, Emily L.; Asadullah, Mariam; Ott, Brooke; Dusza, Patrick; Shah, Tariq A.; Sindhwani, Puneet; Nadiminty, Nagalakshmi; Molinari, Emanuela; Patrizio, Pasquale; Saltzman, Barbara S.; Avidor-Reiss, Tomer (Frontiers in Cell and Developmental Biology, 2021)
A large proportion of infertility and miscarriage causes are unknown. One potential cause is a defective sperm centriole, a subcellular structure essential for sperm motility, and embryonic development. Yet, the extent to which centriolar maladies contribute to male infertility is unknown due to the lack of a convenient way to assess centriole quality. We developed a robust, location-based, ratiometric assay to overcome this roadblock, the Fluorescence-based Ratiometric Assessment of Centrioles (FRAC). We performed a case series study with semen samples from 33 patients, separated using differential gradient centrifugation into higher-grade (pellet) and lower-grade (interface) sperm fractions. Using a reference population of higher-grade sperm from infertile men with morphologically standard sperm, we found that 79% of higher-grade sperm of infertile men with substandard sperm morphology have suboptimal centrioles (p=0.0005). Moreover, tubulin labeling of the sperm distal centriole correlate negatively with age (P=0.004, R=-0.66). These findings suggest that FRAC is a sensitive method, and that patient age and sperm morphology are associated with